If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(2x + -4) + 6 = 3 Reorder the terms: 3(-4 + 2x) + 6 = 3 (-4 * 3 + 2x * 3) + 6 = 3 (-12 + 6x) + 6 = 3 Reorder the terms: -12 + 6 + 6x = 3 Combine like terms: -12 + 6 = -6 -6 + 6x = 3 Solving -6 + 6x = 3 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '6' to each side of the equation. -6 + 6 + 6x = 3 + 6 Combine like terms: -6 + 6 = 0 0 + 6x = 3 + 6 6x = 3 + 6 Combine like terms: 3 + 6 = 9 6x = 9 Divide each side by '6'. x = 1.5 Simplifying x = 1.5
| 17x-8=301.4 | | 3x+6=60.6 | | (24+12/x)-6= | | -x+4y=-24 | | T=273+tc | | 8+5n-3=5n+26-3n | | -40=4.9t^2-17t | | T=273+t*c | | 4v^2-36vw+81w^2= | | -0.7-3(3-5.9q)=-5+15q | | 4x-29=105 | | 15-2(y-3)=6(2y+5)-5y | | 120cu=LWH | | 2.9(2x-2)+0.5x= | | (3y+4)2=28 | | 4x-3x-6=7 | | a-(a*.3)=30000 | | 4x-1=3x+1.5 | | 9x^2-30x+25+25=0 | | 19x^8-13x^6+3x^5= | | x+1x+16x=180 | | 5x-7=8x+77 | | 5x^2+20x+30= | | 23+4x=12 | | 0.5(x-12)+0.2(x+7)=0.3x+3.4 | | 10x-4x=19-7 | | (2w+1)(5-w)=0 | | 0=16t-29t-6 | | 2(u+1)+4u=(2u-1)+8 | | 6x+12=10y | | -2(8y-6)+4y=-2(y+1) | | 2x-21=x-91 |